Pengaruh Motivasi Terhadap Produktivitas Kerja Pegawai Kantor Kependudukan Dan Pencatatan Sipil Kabupaten Enrekang - Henriani, Henriani; Razak, Andi Rosdianti; Parawu, Hafiz Elfiansyah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This research aimed to find out how to increase the motivation of productive civil servants. This study used a quantitative research with a descriptive type which was intended to provide a clear picture of the problems being studied at the Population and Civil Registration office of Enrekang Regency. The sample in this study amounted to 50 people, data collection used a questionnaire. Data analysis used simple linear regression with the help of the computer program Excel Statistic Analysis SPSS v 24.0. The results showed that there was a positive and significant influence between the influence of motivation on work productivity of the employees of the Population and Civil Registration Office of Enrekang Regency. The importance of motivation in increasing the work productivity of employees in the Population and Civil Registration office of Enrekang Regency.Keywords: Motivation, Employee Work Productivity.